2010
DOI: 10.1161/atvbaha.109.196832
|View full text |Cite
|
Sign up to set email alerts
|

ANRIL Expression Is Associated With Atherosclerosis Risk at Chromosome 9p21

Abstract: Objective-We tested the hypothesis that expression of transcripts adjacent to the chromosome 9p21 (Chr9p21) locus of coronary artery disease was affected by the genotype at this locus and associated with atherosclerosis risk. Methods and Results-We replicated the locus for coronary artery disease (Pϭ0.007; ORϭ1.28) and other manifestations of atherosclerosis such as carotid plaque (Pϭ0.003; ORϭ1.31) in the Leipzig Heart Study, a cohort of 1134 patients with varying degree of angiographically assessed coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
318
1
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 406 publications
(343 citation statements)
references
References 27 publications
17
318
1
7
Order By: Relevance
“…The chromosome 9p21 locus is a prominent example: whereas initial studies focused on the two genes situated at the locus, CDKN2A and CDKN2B, current studies rather point to radically new disease mechanisms. Indeed, it appears that the risk/non‐risk alleles at the 9p21 locus relate to different isoforms of ANRIL and subsequently to preferred synthesis of non‐circular/circular forms of this long non‐coding RNA, which affect via ribosomal function the expression of multiple genes leading ultimately to opposing effects on cell proliferation and apoptosis (Holdt et al , 2010, 2013). …”
Section: Genome‐wide Association Studies In Coronary Artery Disease Amentioning
confidence: 99%
“…The chromosome 9p21 locus is a prominent example: whereas initial studies focused on the two genes situated at the locus, CDKN2A and CDKN2B, current studies rather point to radically new disease mechanisms. Indeed, it appears that the risk/non‐risk alleles at the 9p21 locus relate to different isoforms of ANRIL and subsequently to preferred synthesis of non‐circular/circular forms of this long non‐coding RNA, which affect via ribosomal function the expression of multiple genes leading ultimately to opposing effects on cell proliferation and apoptosis (Holdt et al , 2010, 2013). …”
Section: Genome‐wide Association Studies In Coronary Artery Disease Amentioning
confidence: 99%
“…rysms, hypertension, stroke and peripheral artery disease. Recent work has shown that antisense non-coding RNA in the INK4 locus (ANRIL) is transcribed from the Chr9p21 locus and acts as an epigenetic regulator to modulate cardiovascular risks [70]. Functional studies have shown that this lncRNA may be involved in atherosclerotic process, therefore inducing ischemic and hemorrhagic stroke.…”
Section: Lncrna In Vascular Physiological or Pathological Processesmentioning
confidence: 99%
“…The chromosome 9p21 CAD risk haplotype containing multiple single nucleotide polymorphisms (SNP) in tight linkage disequilibrium resides at the 3 0 end of ANRIL gene and exhibits a clear association with ANRIL expression. [15][16][17][18][19] Based on these genetics studies, ANRIL is currently considered as a prime candidate gene for the chromosome 9p21 CAD locus. Subsequently ANRIL is found to be associated with periodontitis, diabetes, open angle glaucoma and various cancers.…”
Section: Introductionmentioning
confidence: 99%